Analysis of patient medication compliance and quality of life of physician-pharmacist collaborative clinics for T2DM management in primary healthcare in China: A mixed-methods study - Xiao, Jie; Wang, Qing; Tan, Shenglan; Chen, Lei; Tang, Bingjie; Huang, Shuting; Zhou, Yangang; Xu, Ping (Frontiers in Pharmacology, 2023)
Background Physician-pharmacist collaboration is a well-established care model for the management of type 2 diabetes mellitus (T2DM) in developed countries, but no study has been conducted in primary healthcare in China. This study aims to evaluate the effects of physician-pharmacist collaborative clinics to manage T2DM in primary healthcare in China, and to better understand the factors influencing the implementation of physician-pharmacist collaborative clinics. Methods Two hundred and sixty-seven patients involved in a 12-month randomized controlled trial were assigned to physician-pharmacist collaborative clinics and usual clinics, completing surveys regarding medication compliance, quality of life (QoL) and care-seeking behavior at the baseline, 3rd, 6th, 9th and 12th month respectively, and diabetes knowledge as baseline and 12th month. A sample of twenty-two Patients, nine physicians and twelve pharmacists participated in semi-structured face-to-face interviews. The quantitative and qualitative data was integrated by triangulation. Results Patients in physician-pharmacist collaborative clinics had significant improvements in medication compliance (p=0.009), QoL (p=0.036) and emergency visits (p=0.003) over the 12-month. Pairwise comparison showed the medication compliance score in the intervention group had been significantly improved at 3rd month (p=0.001), which is more rapidly than that in the control group at 9th month (p=0.030). Factors influencing the implementation of physician-pharmacist collaborative clinics were driven by five themes: pharmaceutical service, team-base care, psychological support, acceptability of care and barriers to implementation. Conclusion Integration of quantitative and qualitative findings showed the effectiveness of physician-pharmacist collaborative clinics in patient medication and QoL in primary healthcare. The qualitative study uncovered barriers in insufficient clinical experience and understaffing of pharmacist. Therefore, the professional training of the primary pharmacist team should be improved in the future.